Uso de realidade aumentada como auxílio para concepção de projetos arquitetônicos em BIM: experimentos de pesquisa aplicada desenvolvida em disciplinas de modelagem e BIM no Curso de Arquitetura e Urbanismo da UFPB entre 2015 e 2017 - Araújo, Alan Nóbrega Dantas de (2018)
This thesis analyzes how Augmented Reality (AR) can help the architectural design process in Architecture Project teaching environment. It seeks to identify, characterize and understand the advantages and disadvantages, difficulties and potentials in use of AR under aspects of hardware, software, use during the architectural design process and student acceptance. AR technologies are in constant development, but least explored as to their benefits and potential applied to the AECO Industry (Architecture, Engineering, Construction and Operation) for designing architectural projects in undergraduate teaching of Architecture. Besides, the constant need to improve project development processes is widely debated, which may justify AR study on immediate opportunities, demands, and potentials. The experiments of this dissertation are applied in three disciplines: Modeling and Prototyping (Postgraduate Program in architecture and Urbanism - PPGAU); Project IV and 3D Modeling (graduation of Architecture and Urbanism - UFPB). The thesis is an applied research, with exploratory and experimental objectives. Seven exploratory experiments are made to define the final experiment. The first two experiments explore techniques of instrumental use, mobile devices, limits of tools, ideal situation of illumination and reading of markers are explored; The following two experiments deal with AR and BIM (Building Information Modeling) used on architectural project design environment; Finally, the three final experiments analyzes the tools to find solutions regarding the use of AR detected in a project workshop. BIM in the interest of this research is treated as a base that can be used in the context of AR. This is due consideration of the tangible aspects on 3D model and building development with potential information. From the seven initial experiments to the final experiment, the protocols were adjusted with improvements in some points considered as difficulties of AR use, during phases of elaboration of architectural projects. In the final experiment, study participants follow protocols for the development and presentation of their projects regarding the use of equipment and software. They are appreciated from the moment of orientation of the students with the teacher until the presentation and visualization of the results obtained in the disciplines. It is possible to understand the results in a qualitative way from analysis of procedures tested in the experiments, direct observations, questionnaire analyzes and focus group discussion. As a result, advantages and disadvantages, as well as current potentials and difficulties with AR tools during the project design process are pointed out. AR using, in this context, was concluded as viable, since adapted according to the protocols that make its use suitable for a more fluid use by the students.